1998
DOI: 10.1053/joca.1998.0147
|View full text |Cite
|
Sign up to set email alerts
|

Production of cartilage oligomeric matrix protein (COMP) by cultured human dermal and synovial fibroblasts

Abstract: These studies demonstrate that substantial amounts of COMP are produced by several mesenchymal cells including synoviocytes and dermal fibroblasts. These findings raise important concerns regarding the utility of measurements of COMP levels in serum or in synovial fluid as markers of articular cartilage degradation because of the likelihood that a substantial proportion of COMP or COMP fragments present in serum or synovial fluid may be produced by cells other than articular chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 0 publications
7
32
0
Order By: Relevance
“…First, we have shown that COMP/TSP5 can bind chondrocytes and serves as an adhesive factor for these cells using short-term attachment assays. This is in agreement with the distribution of COMP/TSP5 close to the chondrocytes in early development in cartilage pericellular and territorial matrix (7,8). Through binding to the chondrocytes, COMP/ TSP5 has the potential to influence cellular activities and cellular phenotype.…”
Section: Discussionsupporting
confidence: 87%
“…First, we have shown that COMP/TSP5 can bind chondrocytes and serves as an adhesive factor for these cells using short-term attachment assays. This is in agreement with the distribution of COMP/TSP5 close to the chondrocytes in early development in cartilage pericellular and territorial matrix (7,8). Through binding to the chondrocytes, COMP/ TSP5 has the potential to influence cellular activities and cellular phenotype.…”
Section: Discussionsupporting
confidence: 87%
“…It has also been identified in the vitreous membrane of the eye (40), tendons (41), vascular smooth muscle cells (42), and the synovium (43,44). In the present study, mRNA for COMP was detected in native synovial explants, but the expression level decreased with culturing time in the absence of a growth factor.…”
Section: Discussionsupporting
confidence: 38%
“…And in patients with rheumatoid arthritis, the COMP gene is expressed in the fibroblast-like cells but not in the macrophages of the synovial connective-tissue layer. 26 COMP is a pentameric noncollagenous glycoprotein which is present not only in synovial [26][27][28] and cartilage tissue, 29 but also in the ocular vitreous, 30 in tendons, 31 and in vascular smooth muscle cells. 32 In the present study, the mRNA for COMP was likewise expressed in bovine synovial tissue.…”
Section: Discussionmentioning
confidence: 99%